KEKERASAN DALAM PACARAN DAN KECEMASAN REMAJA PUTRI DI KABUPATEN PURWOREJO - Ayu, Suci Musvita; Hakimi, Mohammad; Hayati, Elli Nur (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2012)
Background: Gender-based violence in Indonesia is that many cases occur. Since 1998,violence in dating the Rifka Annisa Womens Crisis Center is a case of the second largest afterthe violence against wives. Emotional violence in dating can lead to psychological effects, andone of the psychological effect is the occurrence of anxiety. Anxiety itself can causepsychological effects. The aimof the research to determine the relationship between violence onanxiety in dating young women in Purworejo District.Methods: Cross Sectional study design to girls at SMK SMAN 3 and 6 of Dating Violence (KDP)in Purworejo District 120.Results: The Violence of the most experienced young women is sexual violence because ofbeing kissed forcefully by 34.71%. Physical violence from being hit by 30.83%. Violenceeconomy because without the willingness to buy credit for as much as 25.83% and 17.50%experienced emotional abuse because they feel insulted about the treatment the couple whomake it a laughing stock. Age has an effect on anxiety, where anxiety is more risky in womenwho experience sexual violence against a background of 14-16 years of middle age.Conclusion: There was a significant association between dating violence and anxiety in youngwomen in Purworejo District (p=0,0014 RP= 3,1 dan 95% CI=1,5-6,3).Keywords: Dating Violence, Anxiety, Adolescent